THE INFLUENCE OF FOMO ON INVESTOR INVESTMENT DECISION MAKING IN GEN Z AT KOREA INVESTMENT AND SECURITIES INDONESIA PEKANBARU - Rani Amelia Putri; Septian Wahyudi (International Conference On Law And Social Sciences, 2024)
This study aims to determine and analyze the influence of FoMO on investor investment decision making in GEN Z in Korea Investment and Indonesian securities Pekanbaru. In this study using descriptive survey research types and quantitative research methods using SPSS 25 software. The results of this study showed that the FOMO variable with indicators of Fear, Anxiety and Worry got results from respondents with the Agree category. Meanwhile, the Investment Decision variables with indicators of Representativiness, Availability Bias, Anchoring, Overconfidence, Regreat Aversion, Loss Aversion, Mental Accounting and Herding get results from respondents with the Agree category. The results of a simple linear regression study show that FoMO has a significant relationship to investment decisions